Increased Resistance of Bt Aspens to Phratora vitellinae (Coleoptera) Leads to Increased Plant Growth under Experimental Conditions - Hjältén, Joakim; Axelsson, E. Petter; Whitham, Thomas G.; LeRoy, Carri J.; Julkunen-Tiitto, Riitta; Wennström, Anders; Pilate, Gilles (PLOS ONE, 2012)
One main aim with genetic modification (GM) of trees is to produce plants that are resistant to various types of pests. The effectiveness of GM-introduced toxins against specific pest species on trees has been shown in the laboratory. However, few attempts have been made to determine if the production of these toxins and reduced herbivory will translate into increased tree productivity. We established an experiment with two lines of potted aspens (Populus tremula×Populus tremuloides) which express Bt (Bacillus thuringiensis) toxins and the isogenic wildtype (Wt) in the lab. The goal was to explore how experimentally controlled levels of a targeted leaf beetle Phratora vitellinae (Coleoptera; Chrysomelidae) influenced leaf damage severity, leaf beetle performance and the growth of aspen. Four patterns emerged. Firstly, we found clear evidence that Bt toxins reduce leaf damage. The damage on the Bt lines was significantly lower than for the Wt line in high and low herbivory treatment, respectively. Secondly, Bt toxins had a significant negative effect on leaf beetle survival. Thirdly, the significant decrease in height of the Wt line with increasing herbivory and the relative increase in height of one of the Bt lines compared with the Wt line in the presence of herbivores suggest that this also might translate into increased biomass production of Bt trees. This realized benefit was context-dependent and is likely to be manifested only if herbivore pressure is sufficiently high. However, these herbivore induced patterns did not translate into significant affect on biomass, instead one Bt line overall produced less biomass than the Wt. Fourthly, compiled results suggest that the growth reduction in one Bt line as indicated here is likely due to events in the transformation process and that a hypothesized cost of producing Bt toxins is of subordinate significance.